Ureaplasma urealyticum and Mycoplasma genitalium detection and sperm quality: A cross-sectional study in Vietnam - Minh Tam Le; Dac Nguyen Nguyen; Hoang Bach Nguyen; Viet Quynh Tram Ngo; Vu Quoc Huy Nguyen (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Ureaplasma urealyticum (U. urealyticum) and Mycoplasma genitalium (M. genitalium) may colonize the male genital tract. However, the negative effects of these bacteria on overall sperm quality, including semen pH, sperm concentration, motility, morphology, and total sperm count remain unclear. Objective: This study aimed to determine the presence of genital U. urealyticum and M. genitalium in semen and evaluate the effect of these organisms on sperm quality. Materials and Methods: A cross-sectional study was conducted on 380 men from infertile couples at a tertiary university hospital from July 2017 to June 2018. Semen quality was analyzed according to the World Health Organization 2010 standard, and U. urealyticum and M. genitalium were detected in the semen samples using polymerase chain reaction. Results: 338 men (88.9%) presented with at least one abnormal semen parameter. The detection rates of U. urealyticum and M. genitalium were 16.05% and 0.79%, respectively. There was no significant difference between the Ureaplasma-positive group and the Ureaplasma-negative group in terms of sperm characteristics. Sperm motility and sperm vitality in the Mycoplasma-positive group were much lower than those in the Mycoplasma-negative group (p = 0.02 and p < 0.001, respectively). Conclusion: The presence of U. urealyticum in the semen of infertile men did not affect the sperm characteristics. Although the positive rate of M. genitalium was low, colonization by these bacteria was more likely to negatively affect sperm quality.